PENGARUH PENDAPATAN ASLI DAERAH TERHADAP LAJU PERTUMBUHAN EKONOMI DI KABUPTEN LEBAK - Roby Yudho Wibowo; Euis Yunitasari (The Asia Pacific Journal Of Management Studies, 2016)
Economic development is one of the problems that exist in a country. Development aims to achieve social prosperity through economic growth. Economic growth is the output produced from a variety of sectors and provide a description of how the progress or deterioration that has been achieved in the sectors of the economy in a given period. One of the factors that can enhance economic growth is revenue.            The purpose of this study was to determine the extent to which the local revenue effect in the rate of economic growth in the swampy district. The object of this study conducted at the Department of Revenue and Fiscal Management Lebak regency period of 2008 - 2015. The data used in this research is secondary data obtained from the Department of Revenue and Fiscal Management and Regional Development Planning Board. Data analysis technique used is simple regression analysis using the computer program SPSS v.20.            Based on the results of data analysis showed that the variables PAD positive and significant effect on the level of 5% on the rate of economic growth that is with a coefficient of 0.637 and showed a significant number of 0.000.            Based on the above results, it can be concluded that the original income in this study, positive and significant effect on the rate of economic growth means that, increasingly, the regional revenue will increase Economic Growth in swampy district. Suggestions in this research is to increase revenue, the government hopes to attract investors to be able to improve / create jobs which decrease the unemployment rate.